2013
DOI: 10.1128/iai.00863-12
|View full text |Cite
|
Sign up to set email alerts
|

Use of Site-Directed Mutagenesis To Model the Effects of Spontaneous Deamidation on the Immunogenicity of Bacillus anthracis Protective Antigen

Abstract: c Long-term stability is a desired characteristic of vaccines, especially anthrax vaccines, which must be stockpiled for large-scale use in an emergency situation; however, spontaneous deamidation of purified vaccine antigens has the potential to adversely affect vaccine immunogenicity over time. In order to explore whether spontaneous deamidation of recombinant protective antigen (rPA)-the major component of new-generation anthrax vaccines-affects vaccine immunogenicity, we created a "genetically deamidated" … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
32
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(33 citation statements)
references
References 28 publications
1
32
0
Order By: Relevance
“…The purified rPA proteins obtained using this procedure were approximately 95 to 99% pure as determined by SDS-PAGE. We have previously shown that wild-type rPA exhibits only minor amounts of deamidation (8).…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…The purified rPA proteins obtained using this procedure were approximately 95 to 99% pure as determined by SDS-PAGE. We have previously shown that wild-type rPA exhibits only minor amounts of deamidation (8).…”
Section: Methodsmentioning
confidence: 99%
“…The residues that were changed were Asn 408 , Asn 466 , Asn 537 , Asn 601 , Asn 713 , and Asn 719 . We have used this "genetically deamidated" form of the protein as a model for the naturally deamidated form of the protein that would be expected to result upon prolonged vaccine storage (8). In that previous study, we demonstrated that six-Asp mutant rPA possesses lower immunogenicity than wild-type rPA.…”
mentioning
confidence: 99%
See 3 more Smart Citations